Arduino-based Real Time Implementation of Smart Trash Collector using Internet of Things (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Nowadays certain actions are taken to improve the level of cleanliness in the country. People are getting more active in doing all the things possible to clean their surroundings. When the garbage will reach the maximum level, a notification will be sent to the municipality office, and then the employees can take further actions to empty the bin. This system will help in cleaning the city in a better way. Garbage bins remain uncollected for long periods of time putting the lives of marketers at risk in an event that there is Cholera outbreak especially during the rainy season. In order to avoid such a situation, this project proposes the design and implementation of a GPS and IOT Based Garbage and Waste Collection Bin Overflow Management System using GPS and IOT technology in providing real time information on the status of the garbage bins, i.e. when they are full so that appropriate action can be carried out. The system notifies the person (Truck Driver) in charge of garbage collection by sending a short message (sms) and telling them where the full bin is exactly located. The proposed system having IR sensor once human came to nearby bin, it automatically detects and open bin door using servo motor. At the top of the bin having ultrasonic sensor it measures the level of the bin and automatically send live location using GPS to municipal servers using IOT mode. All components are associated to micro controller Arduino. Arduino ATMEGA328 micro controller used to process input and produce output by using ARDUINO IDE with Embedded C programming and operated through Regulated power supply which gives 5v of DC voltage to all hardware modules.